The Role of Diplomatic Correspondences (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Diplomatic correspondences are pivotal in international relations, serving as the primary medium for formal communication between states and their representatives. This article explores the functions and significance of diplomatic correspondences, including their role in facilitating communication, establishing trust, documenting agreements, and managing crises. Through qualitative analysis of various types of diplomatic documents, this study highlights the essential nature of these correspondences in maintaining effective diplomatic relationships and navigating complex international interactions.